Pediatric anxiety disorders - Compton, Scott N.; Villab, Marianne A.; Kristensen, Hanne (Academic Press, an imprint of Elsevier, 2019)
Pediatric Anxiety Disorders provides a critical, updated and comprehensive overview of anxiety disorders in children and adolescents based on the current state of empirical research. The book provides specific clinical recommendations which integrate new knowledge from neuroscience and innovative delivery formats for interventions. This is the first reference to examine anxiety diagnoses in accordance with the latest edition of the DSM-5, including childhood onset disorders, such as Separation Anxiety Disorder, Selective Mutism, Specific Phobia, Social Anxiety Disorder, Panic Disorder, Agoraphobia and Generalized Anxiety Disorder. The book assists clinicians in critically appraising the certainty of the evidence-base and the strength of clinical recommendations.--from the Publisher.